2004
DOI: 10.1111/j.1349-7006.2004.tb02196.x
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Helicobacter pylori induces apoptosis and inhibits proliferation of heterotopic proliferative glands in infected Mongolian gerbils

Abstract: Mongolian gerbils infected with Helicobacter pylori (H. pylori) develop heterotopic proliferative glands (HPGs) in the glandular stomach submucosa. To investigate the effects of H. pylori eradication on cell turnover in HPGs, three antibiotics, lansoprazole, amoxicillin and clarithromycin, were administered at 50 or 75 weeks after inoculation of H. pylori, and the stomachs were excised for histological examination at 1, 2, 4, 8 or 25 weeks thereafter. The HPGs were classified into gastric type (G-type) and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…17 Cao et al 23 reported that antimicrobial therapy induces apoptosis and inhibits proliferation in H. pylori-infected gerbil gastric mucosa. However, the effect of H. pylori eradication on pre-malignant (eg, dysplasia) and malignant histological lesions was not examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Cao et al 23 reported that antimicrobial therapy induces apoptosis and inhibits proliferation in H. pylori-infected gerbil gastric mucosa. However, the effect of H. pylori eradication on pre-malignant (eg, dysplasia) and malignant histological lesions was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…21 This regimen was selected based on previous studies demonstrating the efficacy of this therapy for H. pylori eradication in infected gerbils. 22,23 Sham therapy consisted of 500 ml sterile water delivered daily for 14 days. Infected and uninfected gerbils, treated with antibiotics or water, were euthanized 8 weeks post-treatment (Figure 1).…”
Section: H Pylori Challenge and Antibiotic Therapymentioning
confidence: 99%
“…However, most in vitro studies have shown the opposite result, that is, apoptosis prevails rather than proliferation after H. pylori or its supernatants treatment. Therefore, it is suggested that increased cell proliferation in gastric epithelium in vivo might be an indirect or secondary response to H. pylori infection [43][44][45]. Together with the previous publications that suppressed apoptosis might be one of major pathogenic factors in H. pylori-associated carcinogenesis [46][47][48] and oncogenic stem cells contributed to H. pylori-associated carcinogenesis [49], we could conclude that the reemergence of Shh expressing cells can explain these compensatory or counteractive privileges of proliferation through imbalanced epithelial turnover and this anti-apoptotic steps and proliferative privileges through Shh reactivation could be the necessary path for H. pylori-associated carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Samples (0.8 mL) containing approximately 1.0 × 10 8 colonyforming units per mL were used as the inoculum, as described earlier. (16)(17)(18)(19) Uninfected gerbils underwent sham inoculation using the same sterile Brucella broth.…”
Section: Methodsmentioning
confidence: 99%
“…Samples (0.8 mL) containing approximately 1.0 × 10 8 colonyforming units per mL were used as the inoculum, as described earlier. (16)(17)(18)(19) Uninfected gerbils underwent sham inoculation using the same sterile Brucella broth.The animals were divided into two major groups: H. pyloriinfected (Hp[+]), and non-infected (Hp [-]) groups, and each group was subclassified with reference to time of death at 50, 75 and 100 weeks. Finally, the animals (n = 70) were divided into Hp(+)-50-week (n = 18), Hp(+)-75-week (n = 6), Hp(+)-100-week (n = 17), Hp(-)-50-week (n = 19), Hp(-)-75-week (n = 6) and Hp(-)-100-week (n = 4) groups (Fig.…”
mentioning
confidence: 99%